Case report: Acinetobacter baumannii septic arthritis in an immunocompetent infant - Liao, Yi; Xiao, Jiapeng; Fang, Feng; Zhou, Hua; Liu, Lingling; Liu, Xinglou (Frontiers in Medicine, 2023)
Acinetobacter baumannii is gram-negative coccobacilli, mainly causing nosocomial infections with poor prognosis especially in patients with prolonged hospitalization or antibiotics administration. A. baumannii pneumonia is the most common clinical forms and usually occurs in critically ill patients in the intensive care unit. However, septic arthritis caused by A. baumannii is rarely reported. Here, we describe a case of A. baumannii septic arthritis combined with incomplete Kawasaki disease in an infant. The child's chief complaint was a 2-week intermittent fever with poor response to antibiotics. Initial physical examination revealed swollen lymph nodes in the neck, pharynx congestion, and rashes. Combining with the laboratory tests, diagnosis of incomplete Kawasaki disease was considered. After administration of high-dose intravenous immunoglobulin and corticosteroids, the child's fever retreated and periungual peeling appeared simultaneously. Swelling of the right knee occurred 5 days after the fever improved and imaging tests of MRI and ultrasound suggested the existence of infection. Diagnosis of septic arthritis was established subsequently, and arthroscopy was carried out. A. baumannii was finally identified by metagenomics next-generation sequencing of joint draining fluid for pathogenic microorganisms. Treatment with meropenem was then added. The patient was eventually recovered and discharged from the hospital after 23 days treatment of meropenem. Although A. baumannii is not a common bacterium of septic arthritis, this rare infection can still occur in infants. Early diagnosis, pathogenic identification and target antibiotic treatment are important to reduce the occurrence of joint sequelae.